Pontes mistas aço-concreto : estudo de diretrizes para dimensionamento otimizado - Fabeane, Ricardo (2015)
It is widely recognized the great importance that the bridges and viaducts have on road systems. Its main functions are linked to the obstacles transposition, the access improvement and distances decrease, although in some cases the results go beyond these questions and also assign a reference character to this kind of construction, whether by its aesthetic form or by its clear span. Due to the high cost associated with its construction, the choice of an appropriate structural system and an optimized design are key factors in enabling these constructions. Related to small and medium spans bridges and viaducts, although currently the preferred system by Brazilian engineers are in reinforced or prestressed concrete, it is observed that the steel-concrete composite system can be an attractive solution due to its smaller construction time and by the fact that this system is able to combine the advantages of steel elements (such as high tensile strength, industrialized construction, flexibility of forms, high dimensional control and speed of erection) to the advantages of concrete (like good compression resistance, lower economic cost and high mass and stability). Based on these characteristics, the development of this study aims to provide guidelines that result in optimized steel-concrete composite bridges. As a mean to achieving the proposed objectives an optimization problem was formulated in order to minimize the cost per meter of the structure of composite bridges from reducing the weight of the steel girders sets, which was performed by manipulating the section dimensions of these elements. The design check of the bridge elements was performed according to the AASHTO (2012) standard. The implementation of the formulation was followed by the analysis of simple span bridges for different spans and number of girders. The obtained results enabled the identification of parameters that results in an economic design of composite bridges, indicating that the use of criteria based on optimization techniques can produce a significant reduction in the structure costs